(untitled) (Research, Society and Development, 2022)
Applications in the health area, known as these m-health, are important accessories for the management of productive systems, especially with the increase in demand for health services. Therefore, this study aims to develop an application for monitoring queues in an ophthalmology institute located in the São Francisco Valley region. The work performed as prototyping steps with Figma, analysis of the application development with Flutter/Dart and Firebase and evaluation of the management of the alpha version. The evaluation was based on the MARS scale, which obtained the dimension “functionality” with the highest evaluation (3.75) and “aesthetics” as the lowest (3.0). The overall quality was indicated as (3.70), above recommended (3.70). It is concluded that it was possible to develop an application using knowledge and techniques of Software Engineering and Queue Management.